PANEL DATA REGRESSION MODEL FOR PREDICTING ECONOMIC GROWTH BEFORE AND DURING THE COVID-19 PANDEMIC IN EAST JAVA PROVINCE - Susetyoko, Ronny; Satriyanto, Edi; Fadliana, Alfi; Humaira, Fitrah Maharani (PATTIMURA UNIVERSITY, 2023)
Gross Regional Domestic Product (GRDP) is one of the key indicators to determine the economic condition of a region in a certain period. GRDP at constant prices has a positive and significant effect on economic growth . This study aims to predict economic growth in East Java before and during the Covid-19 pandemic based on the structural components of regional revenue and expenditure budget realization using panel data regression with data sources from the Directorate General of Fiscal Balance. The results of this study, the best model is the Fixed Effect Model (FEM) with R-Squared 0.99991 and Adj. R-Squared 0.99987. MSE, MAD and MAPE values on the training data are 338724.9919, 259.7182 and 0.6296 respectively. While the MSE, MAD and MAPE values in the testing data are 1716324.2736, 445.7959 and 1.0692 respectively. At the 95% confidence level, Locally Generated Revenue (LGR), Transfers to Regional and Village Funds (TRVF), and Other Revenue (OR) are not significant in the model or have little effect. But at the 99.9% confidence level, all factors (cross section) have a very significant effect. This can be interpreted that local wisdom, or the characteristics of each region/city has a major contribution to economic growth.